Візантійсько-болгарська війна кінця IX ст.: структурний аналіз - Калініченко, Віталій (Чернівці, Видавництво "Прут", 2015)
At the end of the IX-th century the First Bulgarian Empire was a pretty powerful union. That is, since the beginning of the reign of Simeon I the Great (Συμεών A (о Méyac) (893-927), who led the successful war against the Byzantine Empire and the Serbs First Bulgarian Empire has significantly expanded its borders in Southeast Europe for most of the Balkans and territorial able to go to the three seas: the Aegean, Adriatic and Black. This aspect is very important because at this time the international situation in Europe was very tense, and one of the key foreign policy issues of individual countries, including the Byzantine Empire, Great Moravia was trading, market seeking and intercultural relations in particular. The First Bulgarian Empire that is geographically faced with these governmental entities still constantly in contact with them. Therefore, Byzantium believed that Simon and having taken the throne will take an active Byzantine imperial policy. But the latter decided to further strengthen the power of the country. It is motivated by publicity in politics, both external and internal, between the First Bulgarian Empire and the Byzantine Empire during the ensuing wars for territory and spheres of influence at that time in Central and South-Eastern Europe. In this context, one of the most interesting and most unexplored Simeon wars and the Great War with Byzantium is the end of the IX-th century. That historiography sometimes called bulgarian-hungarian wars, as the latter were the dominant military contingent on the side of the Byzantine Emperor Leo VI. It should be noted that this topic is distinguished by its relevance, as some researchers confronts issues relating to the military aspects of the war, including the question and military battles troops bulgarian king with the military forces of the Byzantine Empire. Discussion on the borders of the First Bulgarian Empire and Great Moravia, whose interests also faced much at this time of the end of the IX-th century further increases the urgency. In addition, this subject very well described in written sources. Archaeological same data that period, including armaments, so far outside the area of interest to researchers, though are pretty important information and can determine the military capabilities of some public entities at this time and follow some mutual influence. The purpose of this study is a comprehensive analysis of the Byzantine-Bulgarian (Bulgarian-Hungarian) wars end of the IX-th century with an emphasis on their military and geopolitical aspects. After analyzing the written sources about the first part of hungarians in international politics Central and Southeastern Europe at the end of the IX-th century the following conclusions. First, cautiously suggests that Simeon war with Byzantium began in 888, and the invasion of hungarians and triple victory over the host of the past Simeon held at 889, the second should acknowledge the fact that most likely occurred two wars which delimited 2-year break. The first act began and ended in 889 and was unhappy for bulgarians. Another was held at 892 and ended in victory for the latter. Significant strength acne have survived from the war with Simeon and pechenegs joined with other forces who went to help Arnulf and settled on the plains in the Middle Danube. Some of them, as the researchers point was rejected Bulgarian-Pechenegs destruction north and settled in the Carpathian Mountains.
Византийско-болгарская война конца ІХ в.: структурный анализ
Byzantin-bulgarian war at the end of IX-th century: structural analysis
Keywords: Візантійська імперія; Перша Болгарська держава; Булгарофігон; печеніги; угри; війна; предмети озброєння